Ministry of Planning and Economic Development and International Cooperation Decree No. 15 Of The Year 2025 = وزارة التخطيط والتنمية الاقتصادية والتعاون الدولى قرار رقم 15 لسنة 2025 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.